Kānsưksā wiwatthanākān hunkrab̨ōk Thai : s̄ư ph̄ưnbān nai phūmiphāk tawantok - Sakdā Pannēngphēt (Mahāwitthayālai Sinlapāk̨ōn : UCOM Group, 1995)
Study on Thai puppet development as folk media in western region of Thailand.